EFEK PERBANDINGAN PUPUK ANORGANIK DAN KOTORAN AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BUNGA KOL (Brassica oleracea Var. Botrytis) - Rizky Wahyudi Batubara; Anis Rosyidah; Siti Muslikah (AGRONISMA, 2021)
Provision of inorganic fertilizers and chicken manure is very important to increase soil fertility and nutrient content in the soil. This study aims to determine the effect of the comparison of inorganic fertilizer and chicken manure on the growth and yield of cauliflower. The study used a Randomized Block Design (RAK) consisting of 7 levels of treatment, namely: Control = Without using Urea and Chicken Manure, N1 = 100% Urea, N2 = 50% Urea + 50% ZA, N3 = 75% Urea + 25 % Chicken Manure, N4 = 50% Urea + 50% Chicken Manure, N5 = 25% Urea + 75% Chicken Manure, and N6 = 100% Chicken Manure. Parameters observed were: plant height, number of leaves, stem diameter, total plant fresh weight, root fresh weight, stem fresh weight, leaf fresh weight, crop fresh weight, markatabel yield, crop diameter, total plant dry weight, root dry weight. , stem dry weight, leaf dry weight, crop dry weight, and total flower soluble solids. The results showed that in general the treatment of N6 (100% Chicken Manure) could increase the growth and yield of cauliflower plants.